Sensory Stimulation : Sensory-Focused Activities for People with Physical and Multiple Disabilities. - Fowler, Susan (Jessica Kingsley Publishers, 2006)
We learn about the world constantly through our senses and by interacting with it. Children explore and play in different environments and in doing so they find out what burns them or hurts them, what can be eaten, which things smell nice and what different sounds signify. This process of exploration and learning continues throughout our lives. Because of physical, sensory or intellectual disabilities many people have not had the same opportunities to explore and interact with their environment. Sensory stimulation programmes are designed to provide environments in which people with disabiliti.